TGF-β1 Induces the Dual Regulation of Hepatic Progenitor Cells with Both Anti- and Proliver Fibrosis - Ai-Ting Yang; Dou-Dou Hu; Ping Wang; Min Cong; Tian-Hui Liu; Dong Zhang; Ya-Meng Sun; Wen-Shan Zhao; Ji-Dong Jia; Hong You (Stem Cells International)
Transforming growth factor-beta 1 (TGF-β1) plays a central role in hepatic progenitor cells- (HPCs-) mediated liver repair and fibrosis. However, different effects of TGF-β1 on progenitor cells have not been described. In this study, both in vitro (HPCs cocultured with hepatic stellate cells (HSCs) in transwells) and in vivo (CCl4-injured liver fibrosis rat) systems were used to evaluate the impacts. We found that HPCs pretreated with TGF-β1 for 12 hours inhibited the activation of HSCs, while sensitization for 48 hours increased the activation of HSCs. Consistent with these in vitro results, the in vivo fibrosis rat model showed the same time-dependent dual effect of TGF-β1. Regression of liver fibrosis as well as normalization of serum aminotransferase and albumin levels was detected in the rats transplanted with HPCs pretreated with TGF-β1 for 12 hours. In contrast, severe liver fibrosis and elevated collagen-1 levels were detected in the rats transplanted with HPCs pretreated with TGF-β1 for 48 hours. Furthermore, the TGF-β1-pretreated HPCs were shown to deactivate HSCs via enhancing SERPINE1 expression. Inhibition of SERPINE1 reversed the deactivation response in a dose-dependent manner.